MISREPRESENTATION OF THE INDONESIAN ULEMA COUNCIL IN FATWAS ON SHI'A: NORMAN FAIRCLOUGH MODEL OF CRITICAL DISCOURSE ANALYSIS - Ridwan, Muhammad; Arifudin, Arifudin; Varhah, Eva; Anis, Muhammad Yunus; Arummi, Afnan; Hidayati, Tri Yanti Nurul; Nugraha, Reza Sukma; Luthfi, Khabibi Muhammad (Universitas Negeri Makassar, 2024)
This writing aims to synthesize the misrepresentation strategy presented by the MUI in its fatwa on Shia. This writing is a descriptive qualitative type with a critical paradigm approach. The data sources for this writing are the Central Indonesian Ulema Council's 1984 Fatwa on Shia Beliefs and the 2012 East Java Provincial Indonesian Ulema Council's Fatwa on the Deviance of Shia Teachings. The research data consists of the vocabulary and grammar utilized and selected by the MUI in the fatwa on Shia. This issue is examined through Norman Fairclough's critical discourse analysis, including the experiential value and relational value of vocabulary and grammar. The results of this research show that the MUI, in its fatwa on Shia, displays and orchestrates with an excommunication approach. The fatwa succeeds in expressing the practice of domination by the fatwa producers over the followers of Shia beliefs. The fatwa successfully becomes a discourse that holds power. This is represented through linguistic units referenced to Shia beliefs. The MUI chooses and supports Sunni beliefs while marginalizing Shia beliefs. The representation of the linguistic units utilized by the MUI presents Shia beliefs as incorrect while portraying Sunni beliefs as correct. This shows the presence of misrepresentation or incorrect depiction by the text producers. This strategy is called a misrepresentation strategy. The model of misrepresentation employed by the MUI includes marginalization, delegitimization, and exclusivity.MISREPRESENTATION OF THE INDONESIAN ULEMA COUNCILIN FATWAS ON SHI'A: NORMAN FAIRCLOUGH MODEL OF CRITICAL DISCOURSE ANALYSIS